ANALISA KESIAPAN PEMERINTAHAN DAERAH DALAM MEWUJUDKAN SMART VILLAGE - Hermanto Rohman; Dina Suryawati; Anwar; Agus Suharsono (Halu Oleo University, 2024)
The study was carried out regarding public services, especially opportunities for developing village government innovation through Smart Villages in Jember Regency. The aim of this research is to provide an overview of the results of identifying regional readiness in implementing the Smart Village program and to design a Smart Village model that is in accordance with the results of the village readiness analysis in Jember Regency. The method used in this research is the model-building method, a method intended to produce or develop concepts within the scope of a particular study. Smart village development in Jember Regency needs to pay attention to three levels: enabler, driver and mediator. Important variables include the preparation of regulations and development roadmaps as a reference for service and data integration, as well as the provision of infrastructure using a top-down and bottom-up approach. It is also important to develop an institutional model that involves village government and community participation, as well as increasing human resource capacity which is currently not well structured. Apart from that, it is necessary to develop networks in blank spot areas by involving the Ministry of Communication and Information and collaborating with private providers.